A mathematical model on improved material removal mechanism in fixed agglomerated diamond abrasive lapping - Chen, Jiapeng; Peng, Yanan; Wei, Ying; Ding, Yulong; Dai, Ke; Liu, Bing; Bie, Wenbo; Su, Jianxiu (Precision engineering, 2025)
The manufacture of agglomerated diamond (AD) abrasives involves the combination of ceramic adhesives with single - crystal diamond (SCD) abrasives. This combination results in an abrasive that plays a pivotal role in the semiconductor production process, thus making it an integral material in the manufacturing process. Nevertheless, there exists a notable paucity of numerical and analytical models capable of comprehensively and precisely expounding upon the enhanced material - removal mechanism in the processing of lapping superhard and brittle semiconductor workpieces with fixed AD abrasives. In this treatise, the AD abrasive is ingeniously converted into an equivalent SCD abrasive. Based on the previous research on the removal model of superhard and brittle materials in the fixed SCD abrasive lapping, this paper has deepened the field. The mechanism of material removal and enhancement in fixed AD abrasive lapping was investigated in detail by using an equivalent single - crystal model. A comprehensive review of the interaction of physical and chemical factors aims to achieve efficient and accurate material removal, providing a theoretical basis and technical guidance for the precision machining of superhard and brittle materials. Through a scrupulous and detailed comparison of the correlations between the penetration depths of the AD and SCD abrasives into the sapphire wafer and the deformations occurring during the yielding process in the two types of abrasives incorporated into the matrix material of the fixed abrasive pad (FAP) that is intended to support the abrasives, an exhaustive exploration is carried out on the mapping between the FAP matrix characteristics and lapping parameters and the abrasive cutting depths. Consequently, the underlying and profound causes for the mechanism of performance improvement of fixed AD abrasive pads during material removal are clearly and systematically elucidated and summarized, thereby providing valuable insights and contributions to the relevant research domain. •Mathematical models on removal rates of agglomerated diamond (AD) and single crystal diamond (SCD) abrasives are compared.•AD abrasives are more likely to induce yield deformation and ductile-to-brittle transform of workpieces compared to SCD.•A larger number of effective AD abrasives are involved in the lapping process compared to SCD abrasives.